Elevated urinary mutagenicity among those exposed to bituminous coal combustion emissions or diesel engine exhaust. (16th August 2021) - Wong, Jason Y. Y.; Vermeulen, Roel; Dai, Yufei; Hu, Wei; Martin, W. Kyle; Warren, Sarah H.; Liberatore, Hannah K.; Ren, Dianzhi; Duan, Huawei; Niu, Yong; Xu, Jun; Fu, Wei; et al.
Abstract: Urinary mutagenicity reflects systemic exposure to complex mixtures of genotoxic/carcinogenic agents and is linked to tumor development. Coal combustion emissions (CCE) and diesel engine exhaust (DEE) are associated with cancers of the lung and other sites, but their influence on urinary mutagenicity is unclear. We investigated associations between exposure to CCE or DEE and urinary mutagenicity. In two separate cross‐sectional studies of nonsmokers, organic extracts of urine were evaluated for mutagenicity levels using strain YG1041 in the Salmonella (Ames) mutagenicity assay. First, we compared levels among 10 female bituminous (smoky) coal users from Laibin, Xuanwei, China, and 10 female anthracite (smokeless) coal users. We estimated exposure–response relationships using indoor air concentrations of two carcinogens in CCE relevant to lung cancer, 5‐methylchrysene (5MC), and benzo[ a ]pyrene (B[ a ]P). Second, we compared levels among 20 highly exposed male diesel factory workers and 15 unexposed male controls; we evaluated exposure‐response relationships using elemental carbon (EC) as a DEE‐surrogate. Age‐adjusted linear regression was used to estimate associations. Laibin smoky coal users had significantly higher average urinary mutagenicity levels compared to smokeless coal users (28.4 ± 14.0 SD vs. 0.9 ± 2.8 SD rev/ml‐eq, p  = 2 × 10 −5 ) and a significant exposure‐response relationship with 5MC ( p  = 7 × 10 −4 ). DEE‐exposed workers had significantly higher urinary mutagenicity levels compared to unexposed controls (13.0 ± 10.1 SD vs. 5.6 ± 4.4 SD rev/ml‐eq, p  = .02) and a significant exposure‐response relationship with EC ( p ‐trend = 2 × 10 −3 ). Exposure to CCE and DEE is associated with urinary mutagenicity, suggesting systemic exposure to mutagens, potentially contributing to cancer risk and development at various sites.